Training of nurse educators in the management of care in pediatric oncology: Narratives from graduates (Research, Society and Development, 2026)
In highly complex contexts such as pediatric oncology, the educational role of nurses is essential for comprehensive care. However, its consolidation as a recognized dimension of professional practice still faces formative and institutional challenges. This study analyzes how nurses perceive the influence of their undergraduate education on the development of their role as educators and how they experience this practice in the management of care in a pediatric oncology hospital. This is an exploratory, qualitative study grounded in the framework of Symbolic Interactionism and Grounded Theory. Semi-structured interviews were conducted with nine nurses who graduated from the Paulista School of Nursing (UNIFESP) and are working at the Pediatric Oncology Institute (IOP/GRAACC). The analysis followed the stages of open, axial, and selective coding. Six categories emerged that highlight the construction of the nurse's educational role from undergraduate studies to daily professional practice. The graduates reported formative experiences marked by the integration of teaching, service, and community, educational practices with patients, families, and teams, and feelings of institutional recognition or insecurity. Education was described as a structuring axis of care, demanding pedagogical skills, empathy, planning, and relational sensitivity. The identity of the nurse-educator is continuously constructed and expressed in the articulation between teaching and care. The findings reinforce the importance of formative practices and institutional policies that value the educational dimension of Nursing and promote continuing education in health services.